2022
DOI: 10.3390/nano12132144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser Process Parameters, Liquid Medium, and External Field on the Synthesis of Colloidal Metal Nanoparticles Using Pulsed Laser Ablation in Liquid: A Review

Abstract: Pulsed laser ablation in liquid, used for nanoparticle synthesis from solid bulk metal targets (a top-down approach), has been a hot topic of research in the past few decades. It is a highly efficient and ‘green’ fabrication method for producing pure, stable, non-toxic (ligand-free), colloidal nanoparticles, which is often challenging using traditional chemical methods. Due to the short time scale interaction between the laser pulses and the target, it is difficult to achieve complete control on the physical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 192 publications
0
16
0
Order By: Relevance
“…Figures 6a and 6b illustrate the TEM image and particle size distribution of Ag NPs generated in a CTAB environment, where the TEM image demonstrates a spherical graphitic shape of Ag NPs with a particle size distribution ranging from (5-70 nm) and the large percentage of NPs are close to one another, resulting in a chain -like pattern [31]. Prior research has shown that laser ablation generation of metal NPs in CTAB produces NPs with inhomogeneous particle size [35]. The tension between successive particle development and CTAB coating determined the size of nanoparticles produced by the CTAB surfactant [9].…”
Section: Tem Imaging Of Ag Npsmentioning
confidence: 97%
“…Figures 6a and 6b illustrate the TEM image and particle size distribution of Ag NPs generated in a CTAB environment, where the TEM image demonstrates a spherical graphitic shape of Ag NPs with a particle size distribution ranging from (5-70 nm) and the large percentage of NPs are close to one another, resulting in a chain -like pattern [31]. Prior research has shown that laser ablation generation of metal NPs in CTAB produces NPs with inhomogeneous particle size [35]. The tension between successive particle development and CTAB coating determined the size of nanoparticles produced by the CTAB surfactant [9].…”
Section: Tem Imaging Of Ag Npsmentioning
confidence: 97%
“…different materials by ultrafast laser ablation technique [1][2][3][4][5]. Significant variations in the morphology of nanoparticles from different materials that were produced under almost similar ablation conditions attracted our attention [6][7][8]. This suggests that the material properties are critical to the physical characteristics of nanoparticles generated during the ablation process [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zhang et al [59] have performed finite element simulations to study the morphology of Si surfaces ablated by ns laser. In addition, the effects of laser irradiation on the morphology of as-formed nanoparticles or nanostructures highlight the significance of specific ablation parameters like wavelength, fluence, pulse width, repetition rate, ablation environment, and so on [7]. Singh et al [60] studied the damage morphology of germanium (Ge) using fs laser pulses and observed the recrystallization effects on the ablated Ge surface.…”
Section: Introductionmentioning
confidence: 99%
“…12 Additional factors such as the liquid medium, target, and external fields also strongly affect the final result. 13,20,21 The ablation medium plays a crucial role in regulating the product outcome. A chemical analysis of Au nanoparticles produced by PLAL in saline solution revealed the presence of halide ions on the nanoparticle surfaces, supporting a hypothesis that halogen anions contribute to colloidal stability by carrying a negative charge.…”
Section: Introductionmentioning
confidence: 99%
“…The collapse of the cavitation bubble results in the ejection of molten or vaporized material into the surrounding liquid, where it condenses into nanoparticles. , PLAL offers partial control over the nanoparticle size, size distribution, shape, and aggregation through the modulation of the parameters, including the laser wavelength, pulse width and rate, and fluence . Additional factors such as the liquid medium, target, and external fields also strongly affect the final result. ,, …”
Section: Introductionmentioning
confidence: 99%